Early Economic Evaluation Demonstrates That Noncomputerized Tomography Robotic-Assisted Surgery Is Cost-Effective in Patients Undergoing Unicompartmental Knee Arthroplasty at High-Volume Orthopaedic Centres - Leo M. Nherera; Sanjay Verma; Paul Trueman; Simon Jennings (Advances in Orthopedics)
Background. For over fifty years, unicompartmental knee arthroplasty (UKA) has been used to treat single-compartment osteoarthritis of the knee and is considered a safe alternative to total knee arthroplasty (TKA). The development and use of robotic-assisted surgery (r-UKA) have made the execution of the procedure more precise, and various studies have reported improved radiographic outcomes and implant survival rates; however, its cost-effectiveness is unknown. This study aimed at assessing the cost-effectiveness of noncomputerized tomography (non-CT) r-UKA compared to the traditional unicompartmental knee arthroplasty (t-UKA) method in patients with unicompartmental knee osteoarthritis from the UK payer’s perspective. Methods. We developed a 5-year four-state Markov model to evaluate the expected costs and outcomes of the two strategies in patients aged 65 years. Failure rates for t-UKA were taken from the British National Joint Registry while data for non-CT r-UKA were obtained from a 2-year observational study. Cost was obtained from the NHS reference cost valued at 2018/19 GBP£, and a discount rate of 3.5% was applied to both costs and benefits. Results. For a high-volume orthopaedic centre that performs 100 UKA operations per year, non-CT r-UKA was more costly than t-UKA but offered better clinical outcomes, and the estimated cost per QALY was £2,831. The results were more favourable in younger patients aged less than 55 and sensitive to case volumes and follow-up period. Conclusion. Non-CT r-UKA is cost-effective compared with t-UKA over a 5-year period. Results are dependent on case volumes and follow-up period and favour younger age groups.